Chemoselection: a paradigm for optimization of organ preservation in locally advanced larynx cancer. Issue 9 (September 2013) - Vainshtein, Jeffrey M; Wu, Vivian F; Spector, Matthew E; Bradford, Carol R; Wolf, Gregory T; Worden, Francis P
Definitive chemoradiation (CRT) and laryngectomy followed by postoperative radiotherapy (RT) are both considered standard-of-care options for the management of advanced laryngeal cancer. While organ preservation with chemoradiotherapy is often the preferred up-front approach for appropriately selected candidates, the functional benefits of organ preservation must be carefully balanced against the considerable morbidity of salvage laryngectomy in patients who fail primary chemoradiation. Up-front identification of patients who are likely to require surgical salvage, therefore, is an important aim of any organ preserving approach in order to minimize morbidity while maximizing organ preservation. To this end, a strategy of 'chemoselection', using the primary tumor's response after 1 cycle of induction chemotherapy as an in vivo method of selecting responders for definitive chemoradiation while reserving primary surgical management for non-responders, has been employed extensively at our institution. The rationale, treatment results and future directions of this approach are discussed.